1989
DOI: 10.1016/0002-9343(89)90255-6
|View full text |Cite
|
Sign up to set email alerts
|

The reply

Abstract: All adult patients with systemic lupus erythematosus (SLE) (greater than or equal to 15 years old, n = 86) from a defined population (approximately 160,000 population at risk) were followed prospectively over 6 years. The study area comprised 2 health care districts served by only 1 hospital. Retrieval was based on clinical case finding and computerized diagnosis and laboratory registers. The incidence of the disease was 4.0 cases/100,000 adults/year and was stable during the 6 years, suggesting that completen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Arthritis and pleuritis are SLE manifestations, often associated with a more pronounced acute phase response [15,44], and patients with these symptoms had a higher risk of developing a first CVE, as also reported by Mok et al [16]. Patients with a previous episode of venous occlusion, a major manifestation of APS [43], were more likely to present with a first CVE.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Arthritis and pleuritis are SLE manifestations, often associated with a more pronounced acute phase response [15,44], and patients with these symptoms had a higher risk of developing a first CVE, as also reported by Mok et al [16]. Patients with a previous episode of venous occlusion, a major manifestation of APS [43], were more likely to present with a first CVE.…”
Section: Discussionmentioning
confidence: 80%
“…However, other studies have shown that patients with SLE have a marked increased risk of CVD as compared to the general population [2,15,50]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…101,102 The increased relative risk is especially striking in young women, with a prospective cohort study estimating that women in the 35- to 44-year-old age group were more than 50 times more likely to have an MI compared with women of a similar age. 102 …”
Section: Slementioning
confidence: 99%
“…SLE patients have a highly increased cardiovascular morbidity and mortality which can only be partly explained by traditional risk factors [2], [3], [4], [5]. Anti-phospholipid (aPL) antibodies are a group of phospholipid-binding autoantibodies with overlapping, but partly different specificities.…”
Section: Introductionmentioning
confidence: 99%